2013
DOI: 10.1902/jop.2012.120238
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐Year Results Following Treatment of Intrabony Defects With an Enamel Matrix Protein Derivative Combined With Either a Natural Bone Mineral or a β‐Tricalcium Phosphate

Abstract: Within their limitations, the present findings indicate that the clinical improvements obtained with regenerative surgery using EMD + NBM or EMD + β-TCP can be maintained over a period of 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 46 publications
5
46
0
2
Order By: Relevance
“…The finding that at 5 years, a CAL gain of ≥4 mm was still measured in 75% (nine of 12) of the defects in both groups compared to baseline indicates that the short‐term results obtained with both treatments can be maintained for a longer period, despite the fact that the addition of PRP did not influence the outcomes obtained with EMD + NBM. Obviously, the regularly provided SPT (between 1 and 5 years, all 24 patients received SPT at least twice per year) substantially contributed to the long‐term stability of the results, corroborating previous findings 6,29‐32 . Moreover, the fact that the clinical improvements were equally maintained in both groups corroborates previous reports and suggests that patient compliance and regularly provided SPT are more important for ensuring long‐term stability than the regenerative approach itself.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The finding that at 5 years, a CAL gain of ≥4 mm was still measured in 75% (nine of 12) of the defects in both groups compared to baseline indicates that the short‐term results obtained with both treatments can be maintained for a longer period, despite the fact that the addition of PRP did not influence the outcomes obtained with EMD + NBM. Obviously, the regularly provided SPT (between 1 and 5 years, all 24 patients received SPT at least twice per year) substantially contributed to the long‐term stability of the results, corroborating previous findings 6,29‐32 . Moreover, the fact that the clinical improvements were equally maintained in both groups corroborates previous reports and suggests that patient compliance and regularly provided SPT are more important for ensuring long‐term stability than the regenerative approach itself.…”
Section: Discussionsupporting
confidence: 88%
“…Another difficulty in finding significant differences between the treatments can be due to the excellent results obtained with the combination of EMD + NBM. The use of EMD + NBM has been demonstrated to promote periodontal regeneration in intrabony defects and result in substantial clinical improvements for both the short and long term (up to 10 years) 1‐6 . The reported histologic and clinical outcomes after the use of EMD + NBM appear to be supported by recent findings from a series of in vitro experiments evaluating the effect of EMD coating of NBM particles on downstream cellular pathways such as adhesion, proliferation, and differentiation of PDL cells and primary human osteoblasts 7 .…”
Section: Discussionmentioning
confidence: 81%
“…, Döri et al. ). Surprisingly, there are only few data regarding AgP and they are not always encouraging (DiBattista et al.…”
Section: Discussionmentioning
confidence: 98%
“…A significant clinical attachment gain was also achieved and maintained over 6 years in intra‐bony defects in a study performing GTR versus GTR+DBBM (Stavropoulos & Karring, ). Clinical improvements obtained with regenerative surgery using EMD + DBBM or EMD + beta‐TCP could be maintained over a period of 10 years (Dori et al., ). In a systematic review on periodontal regeneration in intra‐bony defects, it was concluded that improvements in clinical parameters are maintainable up to 10 years, consistent with a favourable long‐term prognosis (Kao, Nares, & Reynolds, ).…”
Section: Discussionmentioning
confidence: 99%